PERANGKAT PEMBELAJARAN: KURIKULUM TEMATIK DAN MERDEKA BELAJAR - Dhea Fitri Andayani; Manisa Septi, Misa Sari, Silky Deasty Maulidya (ADISAM PUBLISHER, 2026)
Learning tools for thematic and independent curricula generally encompass various components, such as Lesson Implementation Plans (RPP), Syllabus, Teaching Materials, and Evaluation Instruments. RPP is a planning document that includes learning steps, objectives, teaching materials, methods, media, and evaluation. The Syllabus provides a general overview of the subjects taught, while Teaching Materials include learning materials, assignments, and other learning sources. In thematic curricula, learning tools are developed with an approach that integrates multiple subjects under a common theme, allowing students to study concepts in an integrated manner. Meanwhile, in the Independent Curriculum, learning tools are developed with an approach that integrates various aspects, such as strengthening the Pancasila student profile, intracurricular and extracurricular activities. This enables students to understand these concepts in a broader and more meaningful context.